Barriers and facilitators to improved sedentary behaviour in coronary heart disease patients: a scoping review - Lili Yang; Chen Wu; Yuting Yang; Qiao Yuan (BMJ Open)
Introduction The majority of patients with coronary heart disease (CHD) are at high sedentary levels, which severely affects patient prognosis and outcome. Despite the proven benefits of reducing sedentary behaviour (SB), intervention studies’ effectiveness has been limited. Thus, the factors influencing SB change in patients with CHD need to be explored. This scoping review aimed to identify barriers and facilitators to improved SB in CHD patients and map these factors to the Capability–Opportunity–Motivation-Behaviour model.Methods We conducted a scoping review in accordance with the Arksey and O’Malley framework. Eligibility criteria included qualitative and quantitative studies on SB in patients with CHD. Nine databases were searched (PubMed, Medline, Embase, CINAHL, Web of Science Core Collection, Scopus, CNKI, WanFang and VIP) from inception through 31 December 2023, following the scoping review methodology.Results A total of 24 studies, including two qualitative and 22 quantitative studies, were included, with 15 847 patients. Barriers to improved SB in CHD patients included capability (eg, physical characteristics, lack of knowledge to improve SB), opportunity (eg, lack of partnership support, lack of resources to carry out activities) and motivation (eg, maintaining the habit of SB, impaired belief in activities). Facilitators included capability (eg, exercise session, improving understanding of SB), opportunity (eg, utilisation of support, tele-rehabilitation guidance, diversification of living environments) and motivation (perceived benefit).Conclusions Patients with CHD have unique barriers and facilitators to improving SB. Future research should adequately reduce barriers and promote facilitators to increase the effectiveness of interventions.